1989
DOI: 10.1073/pnas.86.9.3296
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of major histocompatibility complex binding regions of protein antigens by sequence pattern analysis.

Abstract: We have previously experimentally analyzed the structural requirements for interaction between peptide antigens and mouse major histocompatibility complex (MHC) molecules of the d haplotype. We describe here two procedures devised to predict specifically the capacity of peptide molecules to interact with these MHC class II molecules (IAd and IEd). The accuracy of these procedures has been tested on a large panel of synthetic peptides of eukaryotic, prokaryotic, and viral origin, and also on a set of overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(183 citation statements)
references
References 12 publications
5
177
0
1
Order By: Relevance
“…Although Sette and colleagues (16) have shown that a triple-base motif (BXBXB) such as KFKGK, in which 3 positively charged amino acids are separated by 1 or 2 uncharged amino acids, can bind to I-Ed and induce T cell proliferation (f6), we have not studied the sequences within peptide 58-69 that are optimal for stimulation of NZB/W T cells, nor have we proven that they are presented solely by I-Ed. These investigations are in progress.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although Sette and colleagues (16) have shown that a triple-base motif (BXBXB) such as KFKGK, in which 3 positively charged amino acids are separated by 1 or 2 uncharged amino acids, can bind to I-Ed and induce T cell proliferation (f6), we have not studied the sequences within peptide 58-69 that are optimal for stimulation of NZB/W T cells, nor have we proven that they are presented solely by I-Ed. These investigations are in progress.…”
Section: Discussionmentioning
confidence: 89%
“…Sette et a1 (16) showed that a triple-base motif BXBXB (where B is a basic amino acid and X is an uncharged amino acid) can bind the I-Ed class I1 molecule, which NZB/W mice express. The 12-mer contains such a motif, KFKGK.…”
Section: Nzb/w) Female Mouse (43) Inactivation Of Helper T Cells Prementioning
confidence: 99%
“…Based on the observations that the tripalmitoil-S-glycerylcysteinyl-seryl-serine moiety used in the construct of Deres et al ( 13) behaves as a TD,, in another type of construct (18) and the ovalbumin tryptic fragment 229-276, which contains a predicted TDi, according to Sette's algorithm ( 19) and a proven TD, (20) but not the 242-276 (which only contains the TD,) is able to induce CTL in vivo (1 I), we speculated that synthetic colinear peptide constructs of the type TDh-TD, or TD,-TDh might be able to induce CTL in vivo. Ishioka et al (12) have suggested a similar proposition; however, to our knowledge, no experimental evidence has yet been published to validate these hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…PG was isolated from human cartilage, and the GAG side chains were depleted by digestion with chondroitinase ABC (Seikagaku America, Falmouth, MA) as described previously (38,39). Peptide sequence selection was based on the presence of MHC-binding motifs (40), ␣-helix amphipathic sequence motifs that are common in T cell epitopes (41), and the hydrophobic "strip-of-helix" algorithm (42). As a result of this selection, a total of 143 aggrecan core protein-specific peptides (84 located in the G1 domain and 59 in other regions) covering all predicted sites, with a 3-mer offset (43) and ϳ25% nonpredicted regions, were synthesized by the pin method (Chiron Mimotopes, Raleigh, NC).…”
Section: Methodsmentioning
confidence: 99%
“…Also, we were not surprised to identify a few, originally nonpredicted, T cell epitopes. However, we found it interesting that peptides spanning 2 regions of the PG core protein (p22-51 and p253-285) proved to be highly immunogenic in both DR4-and DQ8-transgenic mice, since these sequences were not predicted to be potential T cell epitopes for either DRB1*0401 (46,47) or DQB1*0302 alleles in studies using multiple prediction methods (40)(41)(42). By contrast, a few peptides in the G1 domain and a peptide sequence ( 1785 GAYYGSGTPSSFP) in the chondroitin sulfateattachment region with predicted high-affinity binding to DRB1*0401, which were selected as strong T cell epitopes (46,47), were found not to be recognized in the humanized mice.…”
mentioning
confidence: 92%